Smartphone-based services, perceived accessibility, and transport inequity during the COVID-19 pandemic: A cross-lagged panel study. (August 2021) - Liu, Qiyang; An, Zihao; Liu, Yang; Ying, Wanyun; Zhao, Pengjun
Highlights: 186 family interviews were conducted for survey design and result interpretation. A three-wave cross-lagged model is developed. The ease of using smartphone-based services dominantly influence transport equity. Perceived accessibility to services is a sound indicator for transport equity. New mobility services further excluded and marginalised disadvantaged populations. Abstract: Individuals have experienced various degrees of accessibility loss during the COVID-19 pandemic, which may consequently influence transport equity. However, conventional measurements of accessibility cannot capture individual experiences and perceptions of accessibility. Moreover, since many daily necessities and services can only be acquired online during the pandemic, the ease of using smartphone-based services play an essential role in people's everyday lives. Therefore, this paper investigates the relationship between the ease of using smartphone-based services, perceived accessibility, and perceived transport equity during the pandemic. Based on 186 family interviews, a panel survey with 569 respondents was conducted monthly from February to October 2020 in Kunming, China, and a three-wave cross-lagged panel model was developed to understand the causal relationship between the three constructs. The results indicate that the ease of using smartphone-based services dominantly influence transport equity in the early phase of the pandemic, but its effect faded after the lifting of travel restrictions. Perceived accessibility to services appears a sound indicator for transport equity in the new normal, but perceived accessibility and transport equity are not strongly associated when staying at home is perceived as desirable. Moreover, we found that contemporary practices of smartphone-based new mobility services only favour those who already have convenient access to services and have further excluded and marginalised disadvantaged populations, which urgently require policy interventions.